Proteomic approach to the caracterization of unknown origin male infertility - Pacheco, Rita Carolina (2022)
Infertility affects around 50 million couples worldwide, where male infertility contributes for half of all cases. When no clear causesfor infertilitycanbe found, it is designated of unknown origin(UOMI), including idiopathic(ID)and unexplained male infertility (UMI). Diagnosis of male infertility isfirstlybased on routine semen analysis, an evaluationthat has been shown to havepoor prognostic value. This is especially evident in men with UMI that, despite presenting a normal seminal analysis, arestill infertile,stressing the need to deepen the analysis of sperm functionality in these patients to clarify what might be behind their infertility state.In this project,wefocusedon a detailed characterization of sperm function,that goes far beyondthe conventional analysis, to clarifythis issue. Besidesanalysing functional and bioenergetic parameters such as spermcapacitation, acrosome reaction, chromatin status and mitochondrial functionality, a sperm proteomic analysis was alsoperformedusing sequential window acquisition of all theoretical mass spectra (SWATH-MS). In addition, lifestyle and medical history of patients were assessed by survey. Symptomsof anxiety and depression were also evaluated through proper surveys.In this study, ID patients besides having significantly decreased sperm concentration, motility and morphology, also presented significantly decreased sperm viability, chromatin integrity and percentage of capacitated cells,comparing to healthy men, with the proteomic results further supporting the differences among these groups.Furthermore, ID patients had significantly increased incidence of urogenital infections and varicocele. Regarding UMI patients, we observedthat their sperm functionality is very similar to that of the healthy individuals, but significantly different from ID patients, whichwas also mirroredat the proteomic level.UMI patients were also observed to have increased incidence of diagnosed depression, when comparing to healthy individuals and ID patients. Finally, the proteins annexin A5, α-crystallin B chain, apolipoprotein H, destrin, NADH-cytochrome b5 reductase 3, platelet-activating factor acetylhydrolase IB subunit α1and transthyretinwere found, for the first time, to significantly differentiate the 3patient groups,hence being good candidates for further studies on UOMI.Overall, this study entailinga unique complete and integrated analysis of 3 groups of individuals’ sperm functionality and proteome, accuratelycategorized, providednew insights and add knowledge on these patients’ infertility unknown aetiology, opening road to future studies in the field.